2020
DOI: 10.1093/biolinnean/blaa142
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of introgression in endemic frogs from thecampo rupestrecontradicts the reduced hybridization hypothesis

Abstract: The campo rupestre ecosystem is considered an old, climatically buffered, infertile landscape. As a consequence, long-term isolation is thought to have played an important role in the diversification of its biota. Here, we tested for hybridization between two endemic leaf frogs from the campo rupestre. We used sequence markers and coalescent models to verify haplotype sharing between the species, to test the existence and direction of gene flow, and to reconstruct the spatiotemporal dynamics of gene flow. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…This process also explains the contemporary geographical distribution of the genetic diversity in Vellozia auriculata bushes (Fiorini et al, 2019) and in the Alvarenga's treefrog (de Oliveira et al, 2021). Introgressive hybridization has also been reported for two Pithecopus monkey‐frogs (Magalhães et al, 2021). da Silva et al (2018), in turn, demonstrated that many species endemic to Brazilian highlands are shared between Quadrilátero Ferrífero in ER and Mantiqueira mountains (located south of the ER).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…This process also explains the contemporary geographical distribution of the genetic diversity in Vellozia auriculata bushes (Fiorini et al, 2019) and in the Alvarenga's treefrog (de Oliveira et al, 2021). Introgressive hybridization has also been reported for two Pithecopus monkey‐frogs (Magalhães et al, 2021). da Silva et al (2018), in turn, demonstrated that many species endemic to Brazilian highlands are shared between Quadrilátero Ferrífero in ER and Mantiqueira mountains (located south of the ER).…”
Section: Discussionmentioning
confidence: 76%
“…Changes in effective population size associated with Pleistocene climate regimes in the SE have also been reported for the Alvarenga's treefrog (de Oliveira et al, 2021) and for the cactus P. aurisetus (Bonatelli et al, 2014; Perez et al, 2016). This indicates that, even for some plants, the OCBIL premise of climatic buffering for the campo rupestre may be unrealistic (Magalhães et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations